2015
DOI: 10.1590/1519-6984.15313
|View full text |Cite
|
Sign up to set email alerts
|

Propolis and swimming in the prevention of atherogenesis and left ventricular hypertrophy in hypercholesterolemic mice

Abstract: Aims: The present study verified the effect of propolis alone and its association with swimming in dyslipidemia, left ventricular hypertrophy and atherogenesis of hypercholesterolemic mice. Methods and Results: The experiments were performed in LDLr-/-mice, fed with high fat diet for 75 days, and were divided into four experimental groups (n=10): HL, sedentary, subjected to aquatic stress (5 min per day, 5 times per week); NAT submitted to a swimming protocol (1 hour per day, 5 times per week) from the 16 th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(49 reference statements)
2
10
0
Order By: Relevance
“…These flavonoids inhibit the enzyme responsible for the biosynthesis of cholesterol by Hydroxymethylglutaryl CoA reductase, as well as the lipogenic enzyme glucose-6-phosphate dehydrogenase and malic enzyme 24,25 . The mice from group HL presented LVH similar to those of studies developed in our laboratory, demonstrating that LDL-/-mice fed high-fat diet developed LVH and atherosclerosis due to the inflammatory process caused by severe dyslipidemia, associated to the decrease of the bioavailability of nitric oxide and of the serum levels of HDL and its antioxidant and anti-inflammatory functions 3,[26][27][28][29] . Furthermore, HL mice presented resistance to insulin, with hyperinsulinemia associated with the increase in serum levels of enzymes AP, AST, and ALT.…”
Section: Discussionsupporting
confidence: 79%
“…These flavonoids inhibit the enzyme responsible for the biosynthesis of cholesterol by Hydroxymethylglutaryl CoA reductase, as well as the lipogenic enzyme glucose-6-phosphate dehydrogenase and malic enzyme 24,25 . The mice from group HL presented LVH similar to those of studies developed in our laboratory, demonstrating that LDL-/-mice fed high-fat diet developed LVH and atherosclerosis due to the inflammatory process caused by severe dyslipidemia, associated to the decrease of the bioavailability of nitric oxide and of the serum levels of HDL and its antioxidant and anti-inflammatory functions 3,[26][27][28][29] . Furthermore, HL mice presented resistance to insulin, with hyperinsulinemia associated with the increase in serum levels of enzymes AP, AST, and ALT.…”
Section: Discussionsupporting
confidence: 79%
“…Although the chemical composition of propolis is affected by the origin and plant resources (Mishima et al, 2005), the properties of propolis always include antibacterial, anti-inflammatory, and anti-oxidative effects (Burdock, 1998). Moreover, propolis has been shown to have hypotensive and cardioprotective effects (Gogebakan al., 2012, Majieneet al, 2006, Silvaet al, 2015). Royal jelly is effective for protecting the reproductive system and exhibits anti-aging, anti-inflammatory, and antibacterial effects (Ramadan and Al-Ghamdi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For the evaluation of the effects of propolis in dyslipidemia, the majority of the in vivo experimental models used a high-fat diet in order to induce an increase in the serum concentration of cholesterol and triglycerides and only one model used sodium nitrate to induce hypercholesterolemia [68]. Another experimental approach was to use genetically engineered animals like APOE2 or LDL r-/-transgenic mice, which develop severe dyslipidemia due to alterations of enzymes and receptors involved in cholesterol metabolism [70][71][72]. In all experiments, the administration of propolis decreased the concentration of total cholesterol, LDL, and triglycerides.…”
Section: Preclinical Studies Investigating the Effects Of Propolis In Metabolic Diseasesmentioning
confidence: 99%
“…Propolis has a high content of antioxidant molecules, being able to decrease lipid peroxidation and the generation of reactive oxygen species with positive effects on the cardiovascular system. Silva et al, 2015 demonstrated that propolis was able to prevent left ventricular hypertrophy (LVH) and atherogenesis in hypercholesterolemic mice, due to its ability to eliminate superoxide and hydroxyl radicals and the reduction of CD40L expression [ 70 ].…”
Section: Mechanistic Studies With Active Constituents From Propolis In Metabolic Diseasesmentioning
confidence: 99%